Photosensitizer-free visible light-mediated gold-catalysed cis-difunctionalization of silyl-substituted alkynes. Issue 11 (21st September 2017) - Deng, Jie-Ren; Chan, Wing-Cheung; Chun-Him Lai, Nathanael; Yang, Bin; Tsang, Chui-Shan; Chi-Bun Ko, Ben; Lai-Fung Chan, Sharon; Wong, Man-Kin
Abstract : A new photosensitizer-free visible light-mediated gold-catalysed cis -difunctionalization reaction is developed. Abstract : A new photosensitizer-free visible light-mediated gold-catalysed cis -difunctionalization reaction is developed. The reaction was chemoselective towards silyl-substituted alkynes with excellent regioselectivity and good functional group compatibility, giving a series of silyl-substituted quinolizinium derivatives as products. The newly synthesized fluorescent quinolizinium compounds, named JR-Fluor-1, possessed tunable emission properties and large Stokes shifts. With unique photophysical properties, the fluorophores have been applied in photooxidative amidations as efficient photocatalysts and cellular imaging with switchable subcellular localization properties.